Stratification Approach to Research Border Economy - Vasily, Vasily; Bilchak, Mikhail (Olsztyn Economic Journal, 2014)
Stratification of the border economy has important scientific value. It is the question of division of the border economy into striations. The stratification of potential and resources of the border region is used in the article. Eight levels of striations are identified: the natural and economic conditions of the border region; the integrity of reproduction base of the border region; the level of development and territorially-oriented branch organization of productive forces; the degree of completeness of production and power cycles; the production and economic specialization of the border region; the level of infrastructure provisions in the border region; the trade and commercial potential of the border region and development of new management forms in the border region. The indicators and a set of possible methods of the assessment of each of the eight levels of striations are suggested by means of the econometric instruments.